Targeting errors and leakage in a large-scale in-kind transfer program: The food friendly program in Bangladesh as an example - Hoque, Mohammad Mainul; Rashid, Shahidur; Bin Khaled, Muhammad Nahian; Chowdhury, Shyamal K. (International Food Policy Research Institute, 2020)
We evaluated a large transfer program in Bangladesh, named the Food Friendly Program (FFP, Khaddo Bandhob Karmasuchi), based on observational data. The program aims to provide nutritional support to poor rural households during preharvest seasons by offering rice at a subsidized price. It is a targeted program where the selection of the beneficiaries takes place through local governments and community consultations. We examined both inclusion and exclusion errors and measured the magnitude of corruption in the program. We found that for every taka spent by the government under the FFP, about 0.88 taka, on an average, reaches the eligible beneficiaries. In addition, we also looked at the regional variations in poverty and redistribution. The program seems to be achieving a high level of targeting efficiency, though spatial heterogeneity remains an important drawback. Our evaluation offers some important policy lessons discussed in detail in the report.